2017
DOI: 10.1111/bcp.13354
|View full text |Cite|
|
Sign up to set email alerts
|

The effects of advanced age and serum α1‐acid glycoprotein on docetaxel unbound exposure and dose‐limiting toxicity in cancer patients

Abstract: Aimα1‐Acid glycoprotein (AAG), which is a major binding protein of docetaxel, is considered to be a determinant for docetaxel pharmacokinetics. However, there are no reports about the impact of serum AAG on pharmacokinetics and pharmacodynamics in elderly patients treated with docetaxel. The aim of this prospective study was to elucidate the effects of advanced age and serum AAG on docetaxel unbound exposure and neutropenia, dose‐limiting toxicity, in cancer patients.MethodsDocetaxel was administered at 60 mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…(31,32) Several retrospective studies suggest that the C max of docetaxel is the driver of neutropenia. (6,(33)(34)(35) This is supported by the fact that, despite the lower plasma AUC of conventional docetaxel compared to CPC634, the incidence of grade 3 or 4 neutropenia in this study was significantly higher during conventional docetaxel treatment (70% for conventional docetaxel versus 3% for CPC634).…”
Section: Discussionsupporting
confidence: 59%
“…(31,32) Several retrospective studies suggest that the C max of docetaxel is the driver of neutropenia. (6,(33)(34)(35) This is supported by the fact that, despite the lower plasma AUC of conventional docetaxel compared to CPC634, the incidence of grade 3 or 4 neutropenia in this study was significantly higher during conventional docetaxel treatment (70% for conventional docetaxel versus 3% for CPC634).…”
Section: Discussionsupporting
confidence: 59%
“…Different studies have investigated the relationship between toxicity after IV docetaxel treatment and high levels of unbound docetaxel and low AAG plasma levels. 10 , 56 Low AAG levels were associated with the development of oral mucositis and rash in breast cancer patients and were predictive for response and better overall survival after treatment with IV docetaxel in another study in NSCLC patients. 57 , 58 However, the fraction of unbound docetaxel is impacted by polysorbate-80 in the IV formulation, which is lacking in the oral docetaxel formulation.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, in the case of pediatric patients, several other factors, such as age and liver function, should be taken into consideration, as the activity of CYP3A4-and hence liver metabolism-could influence the elimination of DOC from the body [38]. In addition, studies examining the pharmacokinetics of DOC have shown that differences in the composition of plasma proteins, especially acid glycoprotein α1, may impact the level of this drug [8,39,40]. Therefore, to improve the efficiency of treatment, it is crucial to develop a methodology that can be applied in TDM studies to allow the adjustment of the optimal dose of DOC in paediatric oncological patients.…”
Section: Application To Real Samplesmentioning
confidence: 99%